Penerapan Pendidikan Karakter Religious dan Mandiri pada Santri Baru di Lingkungan Pondok Pesanten Al- Fusha Pekalongan - Ayu Meilani Saputri; Dr. Muhamad Rifa’i Subhi, S.Pd.I., M.Pd.; Pais Ainul Yaqin (ejournal.nurulqadim.ac.id, 2024)
Pesantren is an Islamic educational institution that has developed into a national educational system. Islamic boarding schools have greatly aided the growth and development of Islam. Pesantren education maintains characteristics such as religious and independent attitudes. The Al-Fusha Islamic boarding school in Kedungwuni, Pekalongan, is the subject of this study. The purpose of this investigation is to find out how Islamic boarding schools instill religious and independent qualities in students. Using qualitative descriptive research, this study found character education in Al-Fusha Islamic boarding schools. The results show that Islamic boarding schools teach students to be religious and independent in their daily activities.